ANALISIS PENERAPAN ELEKTRONIK LAPOR (E-LAPOR) DALAM PELAYANAN PENGADUAN MASYARAKAT (Studi di Kantor Dinas Komunikasi, Informatika dan Statistik Provinsi Bengkulu) - Deni Triyanto; Beni Segerlaksono; Edi Darmawi (Universitas Diponegoro, 2020)
The purpose of this study is to describe the application of the Electronic-LAPOR (E-LAPOR) in Public Complaint Services at the Office of the Communication, Informatics and Statistics Office of Bengkulu Province. The method used in this study is a qualitative descriptive method with data sources namely primary data obtained through observation, interviews and secondary data obtained through data on the E-Report application. The results of this study can be concluded that the application of E-LAPOR in public complaint services at the Bengkulu Province Communication, Informatics and Statistics Office in principle has implemented E-LAPOR services in accordance with Standard Operational Procedures (SOP) as well as indicators of application and service of complaints run well so that the process Community services can be followed up by the Communication, Informatics and Statistics Office of Bengkulu Province in the form of aspirations, suggestions and criticisms or complaints. However, apart from that, there needs to be an increase in human resources in each OPD in Bengkulu Province as well as an increase in socialization to officials as E-LAPOR managers and the general public as service users both directly and through social media because this will affect the results and performance in implementing E-LAPOR.